NILAI TAMBAH CORPORATE SOCIAL RESPONSIBILITY DAN INTELLECTUAL CAPITAL: SEBUAH PERSPEKTIF FOUR VALUE ASSESSMENT - Amirya, Mirna (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2012)
This paper described the added value of Corporate Social Responsibility (CSR) and Intellectual Capital (IC) viewed from the perspective of four value assessment. Four value assessment consisted of economic performance, reputation value, parenting advantage, and spiritual value. The conclusion showed that based on the perspective of four value assessment, added value of economic performance used the formula of Economic Value Added (EVA) for CSR and Value Added Intellectual Capital (VAIC) for IC, reputation value used share prices and reputation quotient, parenting advantage used the company's strategy, and spiritual value used charity value.